Modifying verbal responses of an educable mentally retarded child - Apuada, Aurora T. 1943- (College of Education, University of the Philippines Diliman, 1975)
The objectives of the study are 1) to illustrate teaching procedures in modifying verbal responses of the Subject from his initial responses to the terminal behavior required: the ability to form sentences, 2) to illustrate planned manipulations of the actual response of speaking in complete correct sentences to accelerate desirable elements of the terminal response, and 3) to demonstrate manipulation of the environmental contingencies associated with the desired verbal responses. The actual modification of the verbal behavior focuses on the procedure which leads to the emission of the terminal response, i.e., the subject must be able to speak grammatically correct sentences.